ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT (Studi Kasus pada Perusahan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2015) - Primaputri, Nina; Zulkarnain, Zulkarnain; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2018)
The objective of this research is to analyze the influence of loan interestrate policy toward credit distribution at banking company listed in IndonesiaStock Exchange, to analyze the influence of capital adequacy ratio (CAR) to creditdistribution at banking company listed in Indonesia Stock Exchange to analyzeinfluence return on assets (ROA) on credit disbursement at a listed bankingcompany in the stock exchange, to analyze the effect of non performing loan(NPL) on loan disbursement to a banking company listed on the Indonesia StockExchange to analyze the effect of the loan deposit ratio (LDR) to creditdistribution to a banking company listed on the Indonesia Stock Exchange.The population in this study are all banking companies (banking) listed onthe Indonesia Stock Exchange from 2010-2015, which amounted to 36 companies.While the sample of 29 companies, after using purposive sampling method. Datacollection techniques are based on the variables studied using documentationmethod, while the data collected are about loan interest rate, capital adequacyratio (CAR), return on assets (ROA), non performing loan (NPL) and loan todeposit ratio (LDR) and credit disbursement. Data analysis technique in thisresearch is doubled linear regression.The result of this research concludes that there is no influence of interestrate, return on asset, non performing loan to credit distribution of bankingcompany that listed in Indonesian Stock Exchange for 2010-2015 period. Butthere is the influence of capital adequacy ratio and loan to deposit ratio to creditdistribution of banking companies listed in Indonesia Stock Exchange Period2010-2015.